Resource allocation technique for video streaming applications in the LTE system - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Basukala, Riyaj; Patachaianand, Rachod; Xue, Minjie; Lin, Cheng-Chung (IEEE, 2010)
Long term evolution (LTE) is the next generation wireless system that supports all IP transmission for multimedia services. The quality of service (QoS) requirements of multimedia services are one of the major challenges that need to be addressed by packet scheduling in the LTE system. This paper proposes a new resource allocation technique for real time (RT) video streaming applications in the downlink LTE system. Resource allocation, which is one of packet scheduling techniques, utilizes instantaneous downlink signal to noise ratio (SNR), packet delay and buffer information when determining the amount of radio resources to be allocated to a user. Simulation results show that the proposed technique outperforms opportunistic technique, a resource allocation technique discussed in the literature, by maximizing system throughput, efficiently utilizing the available radio resources and satisfying the QoS requirements of RT video streaming applications at a higher number of users.